Impact of osmotic drought stress on carbon isotope discrimination and growth parameters in three pistachio rootstocks (Pistacia spp., Anacardiaceae) - Esmaeilpour A.; van Labeke M.C.; Boeckx P.; van Damme P. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Pistachio (Pistacia vera L., Anacardiaceae) is one of the major horticultural crops in Iran with high plantation surface areas, and production and export rates. However, growing water deficiency has become a main limiting factor for growth and development, and especially for maintaining yield quality and volume of this crop. In this study, the responses of carbon isotope discrimination (Δ13C) and some growth parameters of three pistachio rootstocks (P. vera cv. Badami, P. vera cv. Sarakhs and P. terebinthus) to different osmotic drought stress levels (-0.1, -0.50, -1.0 and -1.5 MPa) were investigated in a greenhouse experiment carried out at the Faculty of Bio-science Engineering, Ghent University, Belgium. The impact of different rootstocks on leaf Δ13C varied significantly. Results show that P. vera cv. Sarakhs had the highest discrimination for carbon isotopes, whereas P. vera cv. Badami had the middle and P. terebinthus the minimum discrimination values, respectively. An increase in drought stress intensity caused a decrease in leaf carbon isotope discrimination values in all three rootstocks, although these differences were not significant. Drought stress significantly decreased both plant fresh and dry weight, shoot dry weight, root dry weight, leaf area and stem elongation. There also was a significant rootstock effect of treatments on these growth parameters. Under osmotic stress treatments, root/shoot ratio increased significantly. Control plants showed normal elongation growth, but growth was stopped for all drought stress treatments, and differences were significant for all three rootstocks. There were no significant differences between pistachio rootstocks and drought stress treatments for leaf shedding.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)